Impact of climate change on African agriculture: focus on pests and diseases - Dhanush, D; Bett, Bernard K.; Boone, Randall B.; Grace, Delia; Kinyangi, James; Lindahl, Johanna F.; Mohan, CV; Ramírez Villegas, Julián Armando; Robinson, Timothy P.; Rosenstock, Todd S.; Smith, J.; Thornton, Philip K. (2015)
According to the IPCC’s Fifth Assessment Report, changes in the climate over the last 30 years have already reduced global agricultural production by 1 – 5 % per decade relative to a baseline without climate change. In addition, recent studies indicate that even a 2 degrees increase in global temperature will affect agricultural productivity, particularly in the tropics, and this impact will rise with increases in temperature. In this context, this Info Note presents recent evidence on the implications for crops, livestock, and fisheries production, and their associated pests and diseases in Africa.